Data Science-Based Salt Distribution Analysis: Efforts to Map Harvest Absorption for Income Stability of Coastal Farmers - Abd. Wahab Syahroni; Nilam Ramadhani; Wildona Zumam; Badar Said (Research Parks Publishing LLC, 2026)
Salt distribution is one of the important aspects in the supply chain of the national salt industry. CVWM, as one of the salt distribution companies in Madura, has distribution records from 2017 to 2024 that include information on delivery dates, truck numbers, load tonnage, and salt field origins. This historical data holds great potential to be analyzed using a data science approach, particularly through the exploratory data analysis (EDA) stage. The benefit of this research is to provide insights for the company regarding salt distribution patterns that have occurred over the past eight years, and it is designed to conduct descriptive analysis on salt distribution data. The focus of the analysis is directed at three main aspects, namely annual distribution trends, the contribution of each salt field as a supply source, and seasonal distribution patterns. This research produces data visualizations and descriptive statistical analysis on salt distribution data.